Adsorption of mercury(II) using activated carbon produced from Bambusa vulgaris var. striata in a fixed-bed column - Mistar, Eka Marya; Ida Hasmita,; Muslim, Abrar; Supardan, Muhammad Dani (Penerbit Universiti Kebangsaan Malaysia, 2019)
Pollution by mercury dissolved in aqueous media causes a crucial problem for health and environment. In this study, activated carbon from Bambusa vulgaris var. striata was produced by chemical activation using NaOH for mercury adsorption. The effects of mercury initial concentrations namely 50 and 100 mg/L on the breakthrough characteristics of the adsorption process were defined. The mechanism of the adsorption process through the fixed-bed column was fitted to the Thomas model. The activated carbon was characterized by scanning electron microscopy and energy-dispersive X-ray spectroscopy. The adsorption study with a continuous system and using the Thomas model showed that the highest adsorption capacity (q0) of mercury ions is 218.08 mg/g. It can be concluded that activated carbon from Bambusa vulgaris var. striata has a great potential to act as an adsorbent to remove mercury from water.